Patient‐reported outcomes and urodynamic findings in men with persistent lower urinary tract symptoms following robot‐assisted radical prostatectomy. Issue 5 (13th April 2019) - MacKenzie, Kenneth R.; Davis, James; Harding, Christopher; Aning, Jonathan J.
Abstract: Aims: To evaluate the patient‐reported outcome measures (PROMs) and urodynamic findings in men seeking intervention for lower urinary tract symptoms (LUTS) after robotic‐assisted radical prostatectomy (RARP) in a regional referral center for continence surgery. Methods: Consecutive men with post‐RARP LUTS, who were referred for specialist evaluation and urodynamics between December 2012 and October 2017, were evaluated. Men were invited to complete the International Consultation on Incontinence Questionnaire on Male Lower Urinary Tract Symptoms Long Form (ICIQ‐MLUTS) pre‐operatively and at 6, 12 and 18 months post‐RARP. Results: In total 64/860 (7.4%) men post‐RARP were referred for specialist evaluation. There was a significant increase in total ICIQ‐MLUTS and bother scores at 6, 12 and 18 months compared with the baseline in these men ( P < 0.001 and P < 0.05, respectively). Urodynamics identified 41/64 (64%) had urodynamic stress incontinence (USI) only, 2/64 (3%) had detrusor overactivity (DO) only and 11/64 (17%) had a combination of USI and DO. Of those referred to a continence specialist 29/64 (45%) underwent a continence procedure. Conclusions: Patients with bothersome LUTS post‐RARP have higher baseline ICIQ‐MLUTs scores and significant worsening of total scores at all time points compared with the baseline. Routine use of PROMs may identify patients at risk of bothersome symptoms after RARP and prompt earlier referral for further management of their LUTS. Urodynamic evaluation revealed that the most common finding was pure stress incontinence but the range of urodynamic diagnoses highlights the need to perform urodynamics before making treatment decisions for men with LUTS post‐RARP.